Insulin resistance and impaired adipogenesis. (April 2015) - Gustafson, Birgit; Hedjazifar, Shahram; Gogg, Silvia; Hammarstedt, Ann; Smith, Ulf
Highlights Subcutaneous adipose tissue has a finite expansion capacity. Adipose cell expansion (hypertrophic obesity) is associated with abdominal obesity and insulin resistance. The ability to increase subcutaneous adipogenesis is protective. BMP4 regulates both white and beige/brown subcutaneous adipogenesis.